PROSES BERPIKIR SISWA SMP DALAM MENYELESAIKAN MASALAH MATEMATIKA MATERI FUNGSI DITINJAU DARI PERBEDAAN JENIS KELAMIN - Erin Wahyu Wijayanti (Program Studi S1 Matematika UNESA, 2020)
Education is basically an effort to provide certain knowledge and expertise to develop one’s potential due to advance in science and technology. In the 2013 curriculum, mathematics learning teaches students to think logically and be able to think creatively to solve mathematical problems. In learning mathematics and solving mathematical problems, students do the thinking process. The thought process is a process that begins with receiving data, processing, drawing conclusions and recalling that information from students memories. This type of research is a descriptive study with a qualitative approach that aims to describe the thinking process of junior high school students in solving mathematical problems of material functions in terms of gender differences. The data collection methods in this study through written tests and interviews. The subject of this study was conducted on two students, namely one female student who had an equivalent high mathematical ability. The result of this study indicate that there are differences in the thinking processes of male students and female students. There are diffrences in the thinking process of male students and female students in understanding problems with indicators of translating problems into mathematical language, male students by experimenting, while female students by writing mathematical language from what is known. Furthermore, in planning problem solving activities with indicators determining the completion plan carried out, male students directly apply what is known, while female students in a gradual way from what is known then determine the steps for the solution. Keywords: Thinking process, gender, mathematical problems, material function, gender differences